Ohranjanje zaupanja v mrežni javni sferi - Sekloča, Peter (Teorija in praksa, 2020)
The author looks at the chances of maintaining trust in network media and platforms with the help of public forums. The idea is based on the definition of influence as a generalised form of communication that is persuasion only if it continuously maintains trust among public actors by confronting them in front of the public. Participation in the networked public sphere builds on reversibility (interactivity) and reciprocity. However, distributed networks have structural and topographical characteristics that, when combined with platform business models and the entailing personalisation of news, limit the "public visibility" of content. Tensions between universal participation, centralisation of data extraction and automatisation of content distribution and possible connections are leading to a democratic deficit of the networked public sphere.
Keywords: algorithms; algoritmi; influence; mrežna javna sfera; networked public sphere; personalisation of news; personalizacija novic; platforme; platforms; trust; vpliv; zaupanje